“Narratives for Resurrection”: Review of Samuel J. M. M. Alberti, ed. The Afterlives of Animals: A Museum Menagerie - Porth, Emily (Humanimalia, 2014)
Samuel J. M. M. Alberti, ed. The Afterlives of Animals: A Museum Menagerie. Charlottesville and London: University of Virginia Press, 2011. 247 pp. $35 (hb), $18.50 (pb).